Climate-adaptive buildings: Systems and materials. (June 2019) - Zarzycki, Andrzej; Decker, Martina
This article discusses research case studies that deploy physical computing with kinetic, pneumatic, and smart material technologies as vehicles to address the prospects of these technologies and their future impact on resilient and high-performance buildings. It looks into conceptual aspects of an integrated hybrid system that combines both computation approaches and unique opportunities inherent to these hybrid designs.